THE ENVIRONMENTAL TAX: PRINCIPLES AND IMPLEMENTATION IN INDONESIA - Safitra, Dhian Adhetiya; Hanifah, Afif (Jurnal Pajak dan Keuangan Negara (PKN), 2021)
The Covid-19 pandemic and the failure to achieve tax targets over the past 5 years prompted the need to find a new tax base. Environmental tax can be an option for state revenue. This study lists the advantages and challenges of implementing environmental taxes in Indonesia. Apart from that, this research also tries to examine the regulations that might encourage the implementation of environmental taxes in Indonesia. This study finds that the environmental tax applied in Indonesia has not met the criteria generally accepted in the international community.